Loss to follow-up 1 year after lower extremity peripheral vascular intervention is associated with worse survival. (August 2019) - Wang, Grace J; Judelson, Dejah R; Goodney, Philip P; Bertges, Daniel J
Loss to follow-up (LTF) has been associated with worse outcomes after procedures. We sought to identify differences in lower extremity peripheral vascular intervention (PVI) patients with and without LTF, and to determine if LTF impacted survival. Patients in the PVI registry of the Vascular Quality Initiative (VQI) were included ( n = 39, 342), where t -test and chi-squared analysis were used to compare those with and without LTF. Multivariable logistic regression was used to identify factors associated with LTF while Cox regression analysis was applied to compare survival among those with and without LTF. The overall 1-year follow-up rate was 91.6%. LTF patients were more often male, Hispanic, of black race, and had a higher rate of diabetes, coronary artery disease, congestive heart failure, and dialysis. LTF patients had a higher prevalence of critical limb ischemia, underwent popliteal or distal intervention, and were intervened upon urgently. There was also a higher rate of postoperative complications, and a lower rate of technical success for LTF patients. After controlling for center effects, the independent variables associated with LTF included male sex, age, diabetes, dialysis dependence, ASA class 3 or greater, as well as complications requiring admission. Preoperative aspirin, preadmission home living status, prior carotid intervention, and discharge aspirin were protective against LTF. Adjusted survival analysis showed decreased survival in LTF, with those returning face-to-face surviving longer than those with phone follow-up. Efforts should be focused on understanding these differences to improve follow-up rates and help improve overall survival.